Evaluation of A(H1N1)pdm09 LAIV vaccine candidates stability and replication efficiency in primary human nasal epithelial cells - Shcherbik, Svetlana (Vaccine X, 2019)
The recent reduction of live attenuated influenza vaccine (LAIV) effectiveness in multivalent formulations was particularly associated with the A(H1N1)pdm09 component. In the 2017 the WHO vaccine composition committee changed its recommendations for the A(H1N1)pdm09 component to include an A/Michigan/45/2015-like virus. We evaluated effectiveness and quality of newly developed and previous A(H1N1)pdm09 LAIV reassortants through assessment of their thermal and pH stability, receptor binding specificity and replication fitness in primary human airway epithelial cells of nasal origin (hAECN). Our analysis showed that LAIV expressed hemagglutinin (HA) and neuraminidase (NA) from an A/Michigan/45/2015-like strain A/New York/61/2015 (A/New York/61/2015-CDC-LV16A, NY-LV16A), exhibit higher thermal and pH stability compared to the previous vaccine candidates expressing HA and NA from A/California/07/2009 and A/Bolivia/559/2013 (A17/Cal09 and A17/Bol13). Reassortants A/South Africa/3626/2013-CDC-LV14A (SA-LV14A) and NY-LV16A showed preferential binding to α2,6 sialic acid (SA) receptors and replicated at higher titers and more extensively in hAECN compared to A17/Cal09 and A17/Bol13, which had an α2,3 SA receptor binding preference. Our data analysis supports selection of A/New York/61/2015-CDC-LV16A for LAIV formulation and the introduction of new assays for LAIV characterization.